Oral PSORI-CM01, a Chinese herbal formula, plus topical sequential therapy for moderate-to-severe psoriasis vulgaris: pilot study for a double-blind, randomized, placebo-controlled trial. Issue 1 (December 2016) - Yao, Dan-Ni; Lu, Chuan-Jian; Wen, Ze-Huai; Yan, Yu-Hong; Xuan, Mei-Ling; Li, Xiao-Yan; Li, Geng; He, Ze-Hui; Xie, Xiu-Li; Deng, Jing-Wen; Guo, Xin-Feng; Ou, Ai-Hua
Abstract Background To provide evidence that the Chinese herbal medicine (CHM) PSORI-CM01 combined with Western medicine reduces the relapse rate of psoriasis vulgaris (PV), we plan to conduct a large-scale randomized control trial (RCT). In order to improve and perfect the RCT, this pilot study was designed to determine the feasibility and the potential of a modified protocol for the full-scale RCT. Methods Eligible patients with psoriasis vulgaris (PV) were enrolled into a randomized comparison in which all subjects received topical sequential therapy and PSORI-CM01 or placebo for 12 weeks. The primary outcome measure was the relapse rate. Treatment response was computed from Psoriasis Area and Severity Index (PASI), body surface area (BSA), and Dermatology Life Quality Index (DLQI). The secondary outcome measures included time to relapse, time to onset, rebound rate, PASI score, pruritus scores on the Visual Analog Scale (VAS), BSA, DLQI and SF-36 (short form health survey), and incidence of serious adverse events (SAEs). Results Six of 7 (86 %) subjects reached the PASI-50 in the CHM group compared with nine of 10 (90 %) in the placebo group during the treatment period. Among the subjects who reached PASI-50, one out of six subjects (17 %) relapsed in the CHM group during the treatment period compared with six out of nine patients in the placebo group (67 %). No subjects met the rebound criteria. Changes to baseline in the PASI scores were not significantly different between the two groups (t  = 1.764, P  = 0.098). Conclusion Oral PSORI-CM01 combined with topical sequential treatment showed a smaller recurrence rate (P = 0.118 ) than placebo combined with the same topical therapy for moderate-to-severe PV in this pilot study. Trial registration Chinese Clinical Trial Registry (http://www.chictr.org.cn/searchproj.aspx )ChiCTR-TRC-13003233 ; date of registration: 15 April 2013.